2008
DOI: 10.1159/000165102
|View full text |Cite
|
Sign up to set email alerts
|

Navigational Experience Affects Hippocampus Size in Homing Pigeons

Abstract: Homing (racing) pigeons (Columba livia f.d.) are well-known for their homing abilities, which are thought to be based on a genetic predisposition, multimodal learning and spatial cognition. On average, the hippocampus, a forebrain structure that processes spatial information, is larger in homing pigeons compared to other non-homing pigeon breeds or their wild ancestor, the rock dove. Here we show that this characteristic hippocampus volume is dependent on flying and navigational experience. Twenty homing pigeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 66 publications
1
18
0
1
Order By: Relevance
“…Recent studies have also found increases in the relative size of the lateral pallium associated with elaborated spatial behaviour in several species of teleost fishes (Shumway 2008;Costa et al 2011). These results showing that training in spatial tasks and differential experience in natural environments produce morphological and neurochemical learning-dependent plastic changes in the lateral pallium are similar to those found in the hippocampus of amniotes (Jacobs & Spencer 1994;Hampton et al 1995;Basil et al 1996;Healy et al 1996;Ramirez-Amaya et al 1999, 2001Holahan et al 2006;Roth et al 2006;Cnotka et al 2008).…”
Section: Map-like Memories and Hippocampal Pallium In Teleost Fishesmentioning
confidence: 53%
“…Recent studies have also found increases in the relative size of the lateral pallium associated with elaborated spatial behaviour in several species of teleost fishes (Shumway 2008;Costa et al 2011). These results showing that training in spatial tasks and differential experience in natural environments produce morphological and neurochemical learning-dependent plastic changes in the lateral pallium are similar to those found in the hippocampus of amniotes (Jacobs & Spencer 1994;Hampton et al 1995;Basil et al 1996;Healy et al 1996;Ramirez-Amaya et al 1999, 2001Holahan et al 2006;Roth et al 2006;Cnotka et al 2008).…”
Section: Map-like Memories and Hippocampal Pallium In Teleost Fishesmentioning
confidence: 53%
“…
Cnotka et al, 2008; Mehlhorn and Rehkämper, 2009). Several orientation cues and mechanisms -olfactory cues, visual landmarks, sun compass, magnetic compass -are known to be involved in homing behaviour, and parameters such as motivation and experience are also known to be important for fast and successful homing (Papi et al, 1974;Visalberghi and Alleva, 1975; SchmidtKönig, 1990;Bingman, 1993; Lipp, 1996;Walcott, 2005).
…”
mentioning
confidence: 99%
“…There is evidence to suggest that the more exploration of an environment an organism does, the greater the volume of its hippocampus [7,11,12]. In [7] for example, black cab taxi drivers were observed to have larger hippocampus than the average human.…”
Section: Support Of the Hippocampus In Map Buildingmentioning
confidence: 99%